ANALISIS MINAT BACA MAHASISWA STKIP PGRI BANJARMASIN - Hidya Maulida; Wulida Makhtuna; Norliani (Qalam : Jurnal Ilmu Kependidikan, 2023)
This study aimed to describe the reading interest of STKIP PGRI Banjarmasin students as well as the supporting and inhibiting factors of the reading interest. The method used in this study was descriptive qualitative using questionnaire, interview, and documentation. From the results of the study it can be concluded that the reading interest of STKIP PGRI Banjarmasin students is included in the low category. This is evidenced by: (1) 62.85% of students sometimes read before entering class; (2) 18.36% of students have a hobby of reading; (3) 54.46% of students prefer fiction books to scientific texts. Supporting factors are internal and external factors. Internal factors that support students' interest in reading are enjoyment of reading, the desire to always read, the purpose and benefits of reading and the environment, while external factors that support interest in reading are lecturers, the campus environment and the internet. In addition, it is also found that the factors that inhibit interest in reading, namely laziness and technology. Keywords : reading interest, supporting factors, inhibiting factors